Serbia: Regulation of Employment Contracts and Collective Bargaining – Labor and Contract Law Aspects - Dudás, Attila; Jašarević, Senad (Fundamentals of Labor Law in Central Europe, 2022)
The authors give an overview of the current Serbian labor law—the theoretical and practical approach toemployment contracts and collective bargaining. First, the chapter presents basic and supplementary sources of Serbian labor law. Secondly, an overview of the different theoretical approaches to the notion of employment contract in the literature is given. The effective labor law regulation is accentuated, with special regard to the rules of general law of obligations, which is being applied in subsidiary manner. This is followed by an overview of the regulation on collective agreements. A special part of the paper is dedicated to the issue of reforms of labor law in Serbia. In this context, regulatory issues related to employment contracts and collective bargaining are highlighted. Keywords: labor law, employment relationship, employment contracts, collective bargaining